2008
DOI: 10.1186/1471-2407-8-118
|View full text |Cite
|
Sign up to set email alerts
|

CD24 cross-linking induces apoptosis in, and inhibits migration of, MCF-7 breast cancer cells

Abstract: BackgroundThe biological effects of CD24 (FL-80) cross-linking on breast cancer cells have not yet been established. We examined the impact of CD24 cross-linking on human breast cancer cell line MCF-7.MethodsMCF-7 and MDA-MB-231 cells were treated with anti-rabbit polyclonal IgG or anti-human CD24 rabbit polyclonal antibodies to induce cross-linking, and then growth was studied. Changes in cell characteristics such as cell cycle modulation, cell death, survival in three-dimensional cultures, adhesion, and migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
2
13
0
1
Order By: Relevance
“…d Galectin-1 expression in tumor-associated stromal cells but negative reaction in tumoral glands lymphovascular tumor thrombi in our study may support the idea that tumor cells with increased CD24 expression spread more easily because of their capacity to form tumor thrombi with activated platelets and then adhere with endothelial cells at the distal metastatic sites [3]. Conversely, some studies suggested that CD24 cross-linking may inhibit migration, hence tumor progression in breast cancer [36]. Recent studies have reported CD24 expression is closely related with tumor metastasis and poor prognosis in several epithelial neoplasms including non small cell lung [3].…”
Section: Discussionsupporting
confidence: 69%
“…d Galectin-1 expression in tumor-associated stromal cells but negative reaction in tumoral glands lymphovascular tumor thrombi in our study may support the idea that tumor cells with increased CD24 expression spread more easily because of their capacity to form tumor thrombi with activated platelets and then adhere with endothelial cells at the distal metastatic sites [3]. Conversely, some studies suggested that CD24 cross-linking may inhibit migration, hence tumor progression in breast cancer [36]. Recent studies have reported CD24 expression is closely related with tumor metastasis and poor prognosis in several epithelial neoplasms including non small cell lung [3].…”
Section: Discussionsupporting
confidence: 69%
“…We here confirm and expand further the notion that CD24 expression might be a useful marker for human breast carcinoma as it could play a role in facilitating metastasis by the interaction between tumor cells and platelets or endothelial cells (30). In CD24-overexpressing breast cancer cells, CD24 appears to be involved in tumor growth and migration because CD24 cross-linking induces (34). It has been repeatedly suggested that primary luminal breast tumors consists of CD44 pos stem-like breast cancer cells with de novo high invasive and angiogenic capacity, and more differentiated CD24 pos cells.…”
Section: Discussionsupporting
confidence: 70%
“…Fogel et al [21] described CD24 expression as a marker of breast cancer. CD24 protein expression was further described as a prognostic marker in breast cancer [3] important for progression, migration and metastasis of human breast cancer [13,14] . ErbB3 (also known as HER3) is one of the EGF receptors, which regulates the growth, differentiation and survival of human breast epithelial cells [15] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the direction of the screening should be also important to pick up the best candidate as described previously [10] . Taking this point into consideration, 9 genes were picked up from the surface containing CD24 and ErbB3, of which expression in breast carcinomas were extensively described [3,[13][14][15][16][17][18][19] , and listed in Table 2. The orientation of the sphere surface in Fig.…”
Section: Nomination Of Cell Surface Markers Of Breast Cancermentioning
confidence: 99%